2010
DOI: 10.1002/jmr.1097
|View full text |Cite
|
Sign up to set email alerts
|

Insight into molecular imprinting in precipitation polymerization systems using solution NMR and dynamic light scattering

Abstract: Molecular imprinting is a powerful synthetic technique for generating template-defined binding sites in cross-linked polymers. One scientific challenge in molecular imprinting research is to understand the intermolecular interactions leading to molecular complexation and the process of binding site formation during polymerization. In this work, we present a novel method for studying the molecular imprinting process in precipitation polymerization systems. This method employs solution (1) H NMR and dynamic ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Twenty microliters of this mixture were loaded onto the capillary tube in the DLS instrument (Precision Detectors Inc.). The particle sizes expressed as the apparent Z-average (or intensity-weighted) hydrodynamic diameter and polydispersity index, which provides information on the deviation from monodispersity, were measured (28) and compared between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty microliters of this mixture were loaded onto the capillary tube in the DLS instrument (Precision Detectors Inc.). The particle sizes expressed as the apparent Z-average (or intensity-weighted) hydrodynamic diameter and polydispersity index, which provides information on the deviation from monodispersity, were measured (28) and compared between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…This prompted us to seek conditions for the optimization of testosterone‐specific MIPs for high‐binding affinities. Literature data showed that testosterone–MIPs have been synthesized in chloroform (Cheong et al ., ; Noss et al ., ; Gavrilovic et al ., ) and acetonitrile (Rachkov et al ., ; Qiu et al ., ; Long et al ., ). Rachkov et al .…”
Section: Resultsmentioning
confidence: 99%
“…10). Using solution NMR and dynamic light-scattering techniques, Long et al [48] have studied the dynamic process of particle nucleation and growth during precipitation polymerization, and the impact of monomer conversion on the molecular selectivity of the obtained MIP nanoparticles. This study brought new insights to the molecular imprinting process: under well-controlled precipitation polymerization conditions, particle nucleation occurs during the first reaction period, and in the second period the polymerization mainly contributes to increasing intraparticle crosslinking.…”
Section: Preparation Of Mip Nanoparticles and Microspheresmentioning
confidence: 99%